Teaching public administration, public management and policy analysis: some international comparisons - Averch, Harvey; Dluhy, Milan (1997)
This article compares the design and content of domestic and foreign programs for teaching public administration and management. At the Master's level, curriculum designers, irrespective of location, emphasize organization theory, personnel, policy analysis, and microeconomics. However, domestic programs place much more emphasis on research methods and budget management. International programs place more emphasis on public law and management information systems. At this time, neither domestic nor international programs report much required training in leadership, bargaining, or institutional design. - Reproduced
Keywords: Public administration - United States; Public administration - Study and teaching; Public administration